TIPOGRAFI ARAB PEGON DALAM PRAKTIK BERBAHASA MADURA DI TENGAH DINAMIKA KEBUDAYAAN YANG DIUSUNG HURUF LATIN - Naufan Noordyanto (DeKaVe, 2016)
Arabic pegon script or pegon script is the term of a few Hijaiyah/Arabic letters that is generally modified and used to write in Malay and Javanese. In Madura, East Java, Pegon script is used for the writing in the language of Madura and other languages, such as Java language. Unfortunately, practices of writing with Arabic typography Pegon in everyday life today, especially in the area of Madura, still as though vague, because the practice of typography around the world still dominated by "regimes" in Latin script. Pegon script as the focus of typography, is seen as an instrument to realize the visual language. Visuality of language in the form of Pegon script involving practices of language (Madura language). Pegon script actually is the result of "hard work" of efforts to "reconcile" the letter of the culture that was at first considered foreign (Arab-Islamic) with the local culture, especially the language of the local/indigenous (vernacular language). Now, practices of Pegon script can be said of a shift in usage habits. The practice Pegon script initially suspected rolling as a means of spread and transmission of Islamic knowledge, then it took place as an instrument of islamic education (literacy) in islamic students (santri) society, then it also turned increasingly popular and wider scope in the practice for the daily communications. However, in this era of Latin script, pegon script can be said to be marginalized in the corner of the specific socio-cultural environment, and has failed to return “to play” in the global arena, and tend to be replaced with Latin letters that dominate the world of typography practices.